Stock price synchronicity, crash risk, and institutional investors - An, Heng; Zhang, Ting (Journal of corporate finance (Amsterdam, Netherlands), 2013)
Both stock price synchronicity and crash risk are negatively related to the firm's ownership by dedicated institutional investors, which have strong incentive to monitor due to their large stake holdings and long investment horizons. In contrast, the relations become positive for transient institutional investors as they tend to trade rather than monitor. These findings suggest that institutional monitoring limits managers' extraction of the firm's cash flows, which reduces the firm-specific risk absorbed by managers, thereby leading to a lower R2. Moreover, institutional monitoring mitigates managerial bad-news hoarding, which results in a stock price crash when the accumulated bad news is finally released. ► Dedicated institutional investors decrease stock price synchronicity. ► Transient institutional investors increase stock price synchronicity. ► Dedicated institutional investors decrease stock crash risk. ► Transient institutional investors increase stock crash risk. ► Results are consistent with the Jin and Myers (2006) model.